Empowering households decomposing energy inequality in the Philippines - Nemenzo, Julio Anton Mulawin R. (School of Economics, University of the Philippines Diliman, 2019)
Energy is a fundamental part of society and having access to electricity lead to beneficial development outcomes. Using data gathered from 20,591 households from the 2011 Household Energy Consumption Survey prepared by the Philippine Statistics Authority, we examined the presence of inequality in the electricity sector, using the concentration index, an index for measuring welfare services, for measuring electricity inequality. Using this index, this paper aims to see the presence of inequality in the country and to be able to compare the varying levels of inequality in electricity access of households in different regions. Furthermore, this paper decomposes the inequality based on different socioeconomic characteristics such as the highest educational level attained by the household head and their income level. This study found out that there is inequality in all regions, however, regions such as NCR, Region III, and Region I have less inequality than regions such as ARMM, Region IV_B, Region IX. The different socioeconomic variables also indicate other trends of electrical inequality. One of the findings of the decomposition analysis was that being part of the poorest households contributes 49 percent to the overall inequality. Connected to this, education levels of household head contribute to the overall inequality as household heads with college degrees or higher has a 41 percent contribution. In line with these findings, this paper proposes policies which could help improve the education of household heads and electrification programs targeted in regions will more inequality.